Targeting Neurological Manifestations of Coronaviruses by Candidate Phytochemicals: A Mechanistic Approach - Sajad Fakhri; Sana Piri; Mohammad Bagher Majnooni; Mohammad Hosein Farzaei; Javier Echeverría (Frontiers Media S.A., 2021)
The novel coronavirus 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made a wide range of manifestations. In this regard, growing evidence is focusing on COVID-19 neurological associations; however, there is a lack of established pathophysiological mechanisms and related treatments. Accordingly, a comprehensive review was conducted, using electronic databases, including PubMed, Scopus, Web of Science, and Cochrane, along with the author's expertize in COVID-19 associated neuronal signaling pathways. Besides, potential phytochemicals have been provided against neurological signs of COVID-19. Considering a high homology among SARS-CoV, Middle East Respiratory Syndrome and SARS-CoV-2, revealing their precise pathophysiological mechanisms seems to pave the road for the treatment of COVID-19 neural manifestations. There is a complex pathophysiological mechanism behind central manifestations of COVID-19, including pain, hypo/anosmia, delirium, impaired consciousness, pyramidal signs, and ischemic stroke. Among those dysregulated neuronal mechanisms, neuroinflammation, angiotensin-converting enzyme 2 (ACE2)/spike proteins, RNA-dependent RNA polymerase and protease are of special attention. So, employing multi-target therapeutic agents with considerable safety and efficacy seems to show a bright future in fighting COVID-19 neurological manifestations. Nowadays, natural secondary metabolites are highlighted as potential multi-target phytochemicals in combating several complications of COVID-19. In this review, central pathophysiological mechanisms and therapeutic targets of SARS-CoV-2 has been provided. Besides, in terms of pharmacological mechanisms, phytochemicals have been introduced as potential multi-target agents in combating COVID-19 central nervous system complications.